Knowledge sharing in the automotive sector: a comparative study of chinese and brazilian firms - Muniz Jr., Jorge; Hong, Jacky; Oliveira, Stefano; Wintersberger, Daniel; Popadiuk, Silvio (Associação Brasileira de Engenharia de Produção, 2019)
AbstractPaper aims This research aims to evaluate factors that influence knowledge sharing in automotive production context in Brazil and China.Originality Despite the growing recognition of the factors that enable knowledge sharing in organizations, our understanding about the unique challenges encountered by the blue-collar workers in a production context is rather limited. Also, the paper raises issues and challenges involved for production organizations to engage in cross-national knowledge sharing, which remain relatively under-explored.Research method Drawing on the Analytic Hierarchy Process (AHP) approach, we conduct a comparative survey among the production managers in five automotive plants in China and Brazil. The AHP approach is based on Objective: Promote knowledge sharing among production workers; Criteria of knowledge conversion as Socialization, Externalization, Internalization; and Alternatives as Structure, Communication, Training, Incentive, Standard Operating Procedure, Problem Solving Methodology. The methodology focused on the 3 Brazilian and 2 Chinese automotive plants in our fieldwork.Main findings While many authors argue that socialization (dialogue) is the key form of worker knowledge sharing, our findings indicate that workers and managers perceive internalisation as more important in the automotive context. The significant differences between Chinese and Brazilian workers on the relative importance they attributed to knowledge sharing processes and corresponding enabling factors reinforce our understanding about the challenges of knowledge sharing across cultures and lends support to a more particularistic debate of knowledge management. While automotive workers in Brazil preferred to receive more training and better incentive schemes as essential knowledge sharing support mechanisms, Chinese workers valued more standardization through structure and standard operation procedures. The study reaffirms the role of knowledge sharing in continuous improvement and incremental innovation in shop floor operations.Implications for theory and practice In lieu of the gaps in the extant literature, this research aims to further identify and evaluate factors that influence cross-national knowledge sharing in automotive production contexts. The research addressed the gaps to promote supportive ways to provide employees interaction, best practices and lessons learning sharing.
Keywords: Knowledge sharing; Brazil; China; Automotive